The extent of enlarged bronchial arteries is not correlated with the development of reperfusion pulmonary edema after pulmonary endarterectomy in patients with chronic thromboembolic pulmonary hypertension. (November 2020) - Ikubo, Yumiko; Sanada, Takayuki J.; Tanabe, Nobuhiro; Naito, Akira; Shoji, Hiroki; Nagata, Jun; Kuriyama, Ayaka; Yanagisawa, Asako; Kobayashi, Takayuki; Yamamoto, Keiko; Kasai, Hajime; Suda, Rika; et al.
This study investigated whether dilated bronchial arteries are associated with reperfusion pulmonary edema in patients with chronic thromboembolic pulmonary hypertension. Results showed that the extent of enlarged bronchial arteries was not associated with the development of reperfusion pulmonary edema, whereas the residual pulmonary hypertension had a significant association.